ANALISIS SPASIAL-TEMPORAL DAMPAK URBANISASI TERHADAP PERUBAHAN PENGGUNAAN LAHAN, KUALITAS LINGKUNGAN, DAN STRUKTUR SOSIAL EKONOMI DI KOTA JAKARTA TIMUR TAHUN 2005 DAN 2024 - Alaydhiya Yahya, Sofy; Taufiqurrahman Sunariya, M Iqbal; Ihsan Arijudin, 3Basyar; Priyana, Yuli (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2026)
Rapid urbanization in East Jakarta has generated significant environmental and socio-economic challenges, particularly due to land use transformation and increasing population density. This study aims to analyze the impacts of urbanization on environmental quality and community socio-economic conditions, as well as to evaluate the effectiveness of government policies in mitigating its negative effects in 2005 and 2024. The research employs a descriptive qualitative method with a spatial approach and case study design focusing on Cakung, Jatinegara, and Duren Sawit Districts. Data were collected from secondary sources including air quality (PM10), water quality (BOD), land use, and population growth, complemented by interviews and field observations. Data analysis was conducted using content analysis, thematic socio-economic analysis, cross-tabulation, and SWOT analysis. The findings indicate that urbanization has significantly increased residential expansion and reduced green open spaces, leading to higher levels of air and water pollution. Socio-economically, employment has shifted toward informal and service-based sectors, with nominal income growth that remains disproportionate to rising living costs. Policy implementation remains suboptimal due to land constraints and the rapid pace of urban expansion.